2021
DOI: 10.3390/catal11101198
|View full text |Cite
|
Sign up to set email alerts
|

Mo-Doped CuO Nanomaterial for Photocatalytic Degradation of Water Pollutants under Visible Light

Abstract: Recently, metal oxide-based nano-photocatalysts have gained a great deal of attention in waste water remediation due to their outstanding properties. In this report, a novel Mo-doped CuO nanomaterial was successfully prepared and utilized for the degradation of methylene blue water pollutant. The molybdenum content was varied from 1–5 wt.% to obtain the desired modified CuO based nanomaterials. The crystalline structures of as prepared materials were investigated using the XRD technique, which explored the suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…In this equation, “E g ” signifies the optical bandgap energy, “ h ” is the Plank’s constant, “ ” represents frequency, “ ” symbolizes the absorption coefficient and “A” is a constant that depends on transition probability 57 , 58 . Here, n relies on electrons transition and the value of n = 1/2 belongs to direct electrons transition with a direct optical band gap.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this equation, “E g ” signifies the optical bandgap energy, “ h ” is the Plank’s constant, “ ” represents frequency, “ ” symbolizes the absorption coefficient and “A” is a constant that depends on transition probability 57 , 58 . Here, n relies on electrons transition and the value of n = 1/2 belongs to direct electrons transition with a direct optical band gap.…”
Section: Resultsmentioning
confidence: 99%
“…These elements were obtained from the biomolecules that were bound to the surfaces of Ag nanostructures and Ag/ ZnO heterostructures in Aloe vera gel 45,55 . In this equation, "E g " signifies the optical bandgap energy, "h" is the Plank's constant, " ν " represents frequency, " α " symbolizes the absorption coefficient and "A" is a constant that depends on transition probability 57,58 . Here, n relies on electrons transition and the value of n = 1/2 belongs to direct electrons transition with a direct optical band gap.…”
Section: Edx Analysismentioning
confidence: 99%
“…The 3D transition metal incorporated into CuO played a great role in tuning the structure, morphology, and optical properties. Maraj et al 197 reported Mo-doped CuO nanoparticles synthesized by the sol–gel process and utilized it for the degradation of methylene blue under visible light irradiation. Islam et al 198 synthesized Ce-doped CuO nanoparticles through the sol–gel autocombustion method and utilized it for the degradation of methylene blue under the illumination of visible light.…”
Section: Metal Oxide Nanoparticlesmentioning
confidence: 99%
“…For instance, El Sayed, A. M., and Shaban, M. Shaban looked into the effect of Fe-CuO (s) and discovered more excellent activity due to Fe doping [24]. Mo-CuO (s) nanostructures were created by Maraj M. et al, who then assessed their photocatalytic activity against dyes [25].…”
Section: Introductionmentioning
confidence: 99%